2019
DOI: 10.1016/j.neubiorev.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiologic-dose anabolic–androgenic steroid use: A risk factor for dementia?

Abstract: Supraphysiologic-dose anabolic-androgenic steroid (AAS) use is associated with physiologic, cognitive, and brain abnormalities similar to those found in people at risk for developing Alzheimer's Disease and its related dementias (AD/ADRD), which are associated with high brain β-amyloid (Aβ) and hyperphosphorylated tau (tau-P) protein levels. Supraphysiologic-dose AAS induces androgen abnormalities and excess oxidative stress, which have been linked to increased and decreased expression or activity of proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 564 publications
0
17
0
Order By: Relevance
“…Recent evidence, by administrating neuropsychological tests to weightlifters both AAS users and nonusers, demonstrated a cognitive disfunction due to long-term high AAS exposure [ 46 ]. In this regard, oxidative stress and apoptosis due to AASs abuse may lead to neurodegeneration and dementia, especially in long-term users, adolescents and young adults [ 47 , 48 ].…”
Section: Aas Use and Adverse Effectsmentioning
confidence: 99%
“…Recent evidence, by administrating neuropsychological tests to weightlifters both AAS users and nonusers, demonstrated a cognitive disfunction due to long-term high AAS exposure [ 46 ]. In this regard, oxidative stress and apoptosis due to AASs abuse may lead to neurodegeneration and dementia, especially in long-term users, adolescents and young adults [ 47 , 48 ].…”
Section: Aas Use and Adverse Effectsmentioning
confidence: 99%
“…Despite experiencing aesthetic and performance benefits (2, 3), users often report adverse physiological and psychological effects (4)(5)(6)(7)(8), such as lack of impulse control, hostility, and high levels of aggressive and violent behaviors (9)(10)(11). Indeed, a recent meta-analysis of 12 randomized controlled trials has shown that among healthy males, AAS administration increases self-reported aggression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that prolonged AAS use has adverse effects on the brain (12, 36, 37, 39, 42, 43). Using brain scans and brain age prediction based on an independent training set we found evidence of higher relative global, frontal, temporal, occipital and insular brain age in 130 male AAS users compared to 99 male WLC.…”
Section: Discussionmentioning
confidence: 99%
“…Also, compared to non-using weightlifters, AAS-exposed weightlifters have shown to perform poorer on tests assessing working memory (12, 39, 40), executive functions (12, 40, 41), learning and memory (12, 39, 41), processing speed and problem solving (12, 40). Although correlational, such findings have led to the hypothesis that high-dose AAS users are at risk for accelerated brain aging (42, 43).…”
Section: Introductionmentioning
confidence: 99%